ANALISA KOMPARASI KINERJA KEUANGAN SEBELUM DAN SELAMA PANDEMI COVID-19 PADA BANK PEMBANGUNAN DAERAH SE-INDONESIA - Maykel Robi Rantung; Maryam Mangantar; Joy Elly Tulung (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The Covid-19 pandemic has had a broad impact not only on human health but also on the global economy, causing various sectors to face significant challenges, including the banking sector. This study aims to analyze the differences in financial performance before and during the Covid-19 pandemic in Regional Development Banks (BPD) throughout Indonesia for the 2018–2023 period, using financial ratios such as Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Expenses to Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM). This research applies a comparative approach with a quantitative method. The sampling technique used is purposive sampling, and data were analyzed using the Paired Sample T-Test.